FoCup, a secreted protein, is essential for virulence of Fusarium oxysporum f. sp. cucumerinum on cucumber - Xu, Ji-Tong; Liu, He; Li, Shi-Dong; Guo, Rong-Jun; Sun, Man-Hong; Yu, Chao-Ge; Sun, Zhou-Ping; Lu, Xiao-Hong (Frontiers in Microbiology, 2025)
Fusarium oxysporum f. sp. cucumerinum (Foc) infected cucumber (Cucumis sativus), leading to serious wilt disease and great economical losses worldwide. During infection, Foc secreted various protein effectors to facilitate colonization and disease development. Here, we identified a novel virulence effector, designated FoCup, which was highly up-regulated during Foc-cucumber interactions according to transcriptomic data. Bioinformatic analysis using SignalP-5.0 and InterPro predicted an N-terminal signal peptide and a cupredoxin domain in FoCup. Phylogenetic analysis indicated that FoCup is highly conserved within the Fusarium genus. Its secretory capability was experimentally confirmed by the yeast invertase secretion assay. Subcellular localization in Nicotiana benthamiana leaf cells revealed that FoCup-GFP predominantly localized to the plasma membrane, co-localizing with the membrane marker CD3-1007 (AtPIP2A-mCherry). Functional characterization demonstrated that ΔFoCup knockout mutants exhibited significantly reduced virulence on cucumber, accompanied by decreased conidiation, and increased sensitivity to osmotic stressors (e.g., glycerol, sorbitol, NaCl, and KCl). In contrast, mycelial growth remained comparable to the wild-type (WT) strain. The impaired virulence and conidiation in the knockout mutants (ΔFoCup) were fully restored in the complementary mutants (ΔFoCup+FoCup). Specifically, pathogenicity tests showed that the disease index caused by ΔFoCup was significantly reduced by 54.5and 62.5 compared to the wild type Foc, underscoring the critical role of FoCup in pathogenesis. Our findings provide new insights into the molecular mechanisms underlying Foc virulence.